1977
DOI: 10.1093/jnci/59.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative Diseases of Fowl: JM-V Leukemic Lymphoblasts in Cell Culture: Brief Communication2

Abstract: JM-V leukemic lymphoblasts were established in cell culture. The cultured cells (JM-VLC cells) were transplantable in young chicks and produced a disease indistinguishable from JM-V lymphoblastic leukemia as initiated by whole-blood inoculation. JM-VLC cells maintained a normal female karyotype through 13 passages in Rhode Island Red cockerels. With the use of JM-V antisera and antisera from birds with naturally occurring Marek's disease (MD), specific antigens were detected on the surfaces of living cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Cell lines were isolated by preparing single-cell suspensions from nodules in the liver and random sections of tissue from the spleen, thymus, and bursa . These suspensions were diluted into Hahn's medium (22) and cultured at 37°C with 10% C02 for 48 h before transferring cultures at a 1 :5 dilution into ET,OCa, oCk2. Spleen and liver cultures were transferred at a 1 :10 dilution every 24-48 h thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lines were isolated by preparing single-cell suspensions from nodules in the liver and random sections of tissue from the spleen, thymus, and bursa . These suspensions were diluted into Hahn's medium (22) and cultured at 37°C with 10% C02 for 48 h before transferring cultures at a 1 :5 dilution into ET,OCa, oCk2. Spleen and liver cultures were transferred at a 1 :10 dilution every 24-48 h thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of transformed lymphoblastoid cell lines which contain multiple copies of the MDV genome have been established from MDV-induced lymphomas or transplantable lymphomas in chickens (Akiyama et al, 1974;Hahn et al, 1977). There was no amplification of the 132 bp repeat sequence within the BamHI-D and -H regions of latent viral DNA in the transformed lymphoblastoid cells (Hayashi et al, 1988) and the 1-8 kb transcript was produced from the BamHI-D and -H regions of MDV DNA in the transformed cells (Bradley et al, 1989a).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly successful medium was RPMI containing 5% PDS and 5% FCS, while RPMI supplemented with 5 to 15% PDS alone also supported the initial establishment of more cell lines than did RPMI supplemented with FCS alone. With the establishment of chicken cell lines transformed by Marek' s disease virus, several components of the Hahn medium cocktail (Hahn et al, 1977) were bene® cial, but 2-ME was the most critical (Calnek et al, 1978); no comparable requirements were observed with duck cells and, indeed, 2-ME had an inhibitory or toxic effect on duck cells. Following establishment and a period of expansion in the primary medium, the duck cell lines were readily weaned into FCS.…”
Section: Discussionmentioning
confidence: 99%
“…Supplements included: a pool of normal adult duck serum (PDS); foetal calf serum (FCS; Gibco or HyClone, Logan, Utah); 2-mercaptoethanol (2-ME); sodium pyruvate (SP); and tryptose phosphate broth (TPB). Modi® ed Hahn (M H) medium (Hahn et al, 1977) was RPMI containing 8% FCS, 10% PDS, 5% TPB, 1 mM SP and 10 mM 2-ME. Phytohaemagglutinin (PHA) and E. coli lipopolysaccharide (LPS) (both from Sigma, St Louis, Mo) were dissolved in RPMI and used at ® nal concentrations of 5 and 1 m g/ml, respectively.…”
Section: Culture Mediamentioning
confidence: 99%